2020
DOI: 10.1044/2019_jslhr-19-00134
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Intelligibility Deficits in Parkinson's Disease With Perceptual Speech Ratings

Abstract: Purpose This study investigated whether perceptual ratings of speech parameters were predictive of transcription intelligibility in quiet and in noise for speakers with Parkinson's disease (PD). Method Ten speakers with PD and five healthy controls read 56 sentences. One group of 60 listeners orthographically transcribed the sentences in quiet, and another group of 60 listeners transcribed in noise. An additional 23 listeners judged a variety of speech … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Prolonged silences (i.e., over 500 ms) were trimmed and equalization of the audio spectrum in a moving window was subsequently performed. The equalized audios were combined to create the final audio file, which contained an equal number of male and female speakers (Moya-Galé et al, 2018 ), which resulted in 10-talker babble (5 males, 5 females; Chiu and Neel, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prolonged silences (i.e., over 500 ms) were trimmed and equalization of the audio spectrum in a moving window was subsequently performed. The equalized audios were combined to create the final audio file, which contained an equal number of male and female speakers (Moya-Galé et al, 2018 ), which resulted in 10-talker babble (5 males, 5 females; Chiu and Neel, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Intelligibility in individuals with PD is particularly affected in noisy environments, such as dining out at a restaurant or in social gatherings. What is more, a recent study showed that even those individuals with a mild speech disorder may experience a reduction in their intelligibility in the presence of background noise (Chiu and Neel, 2020 ). Multi-talker babble noise is a form of structured background noise that may mask a target speaker's voice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For each recorded sentence, the app automatically embedded the speakers' voice signal into +6-dB signal-to-noise multitalker babble noise [33] to provide an intelligibility score, defined as the percentage of words accurately understood by the ASR system. Automatic feedback on performance was provided at the end of the recording session and not after each sentence to avoid any potential priming effects that could influence sentence production on subsequent items [34].…”
Section: Speech Stimuli and Recording Proceduresmentioning
confidence: 99%
“…These speech changes in prosody (loudness) and articulation have been reported to lead to significant declines in functional communication, communicative participation, and quality of life [6,22,[46][47][48][49][50][51][52][53][54][55]. Neither medical (neuropharmacological or neurosurgical) nor traditional speech treatments, which focus on a range of motor speech symptoms (e.g., respiration, articulation, speech rate, loudness, intonation) in a low dosage mode, have proved consistently or significantly beneficial in improving the degenerative speech or intelligibility of people with PD [56][57][58][59].…”
Section: Introductionmentioning
confidence: 99%